2016
DOI: 10.11648/j.ijnfs.20160504.18
|View full text |Cite
|
Sign up to set email alerts
|

Using Vegetable Puree as a Fat Substitute in Cakes

Abstract: Squash and cantaloupe puree (25,50, 75 and 100%) were used to substitute fat in the production of cake. Cakes prepared with 25% puree (for both squash and cantaloupe) had higher volume than that of control cake. No difference in cake volume was found between control cake and those prepared with 50% puree. At 100% replacement level, cake volume was lowest. Reduced-fat cakes with puree had more moisture and minerals as well as fewer calories than the control. Replacement of baking fat by puree resulted in a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…That was decreased about 4 times in crude ether extract accompanied increased in ash, carbohydrate and crude fiber content (3.92%, 40.08% and 3.33% ,respectively meanwhile decreased in energy value to 241.40 Kcal/100g. These results agree with Hussein 37 who reported the decrease in caloric values and fat in cake prepared with vegetable puree as a fat substitute.…”
Section: Chemical Components Analysis and Minerals Contentsupporting
confidence: 92%
See 2 more Smart Citations
“…That was decreased about 4 times in crude ether extract accompanied increased in ash, carbohydrate and crude fiber content (3.92%, 40.08% and 3.33% ,respectively meanwhile decreased in energy value to 241.40 Kcal/100g. These results agree with Hussein 37 who reported the decrease in caloric values and fat in cake prepared with vegetable puree as a fat substitute.…”
Section: Chemical Components Analysis and Minerals Contentsupporting
confidence: 92%
“…On the other hand, the sensory characteristics affects by the chocolate ingredients such as type of milk and cocoa type and also the manufacturing method which explain that sensory analysis of chocolate spread in this paper may differ due to the difference in the percentage of fat content, ingredients and the processing method. As well Hussein 37 observed that there no differences between the acceptability of cakes made with vegetable puree up to 75% and control cakes. Using of vegetable puree did not accompany by an unwanted color.…”
Section: Sensory Analysismentioning
confidence: 81%
See 1 more Smart Citation
“…The addition of soursop in muffins production needs to be limited because it can affect the muffins' texture and pore size. Soursop fiber can reduce gluten's ability to trap gas which causes the texture of muffins to more rigid, and the pore size is not even (Hussien, 2016). This study aims to obtain the optimum concentration addition of soursop puree and margarine to produce muffins with the best texture, pore size, moisture content, and lowest fat content.…”
Section: Introductionmentioning
confidence: 99%
“…In cake making, shortening performs basic functions such as entrapment of air, a coating of starch and protein molecules, and emulsification of large amount of liquid that contributes to greater crumb moisture and, concomitantly, to the softness of the cake product (Román et al, 2015). Several fat substitutes in baking have been evaluated, such as vegetable oils, modified starches, hydrocolloids as gums in combination with emulsifiers, oleogels and others (Ronda et al, 2011;Patel et al, 2014;Hussien et al, 2016;Doan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%